"It was important not to Ask": Silence in Colm Tóibín's "Long Island" - Carregal-Romero, José (Journal of English Studies, 2024)
Drawing on various theories and approaches, from its application to fiction to its socio-cultural dimensions and presence within communication, this study considers Colm Tóibín’s use of silence as a key narrative element and aesthetic practice in Long Island (2024), inviting some comparisons with its prequel, Brooklyn (2009). As shall be explained, silence operates on different levels in Long Island. Thanks to Tóibín’s tightly controlled release of information, silence becomes crucial to plot development and suspense, and vividly recreates the tensions between concealment and revelation. Silence, too, works for the sake of characterisation, and serves to dramatise the protagonists’ crises and indecisions, as well as their strategies of manipulation. On some other occasions, though, silence contributes to mutual understanding, increasing closeness and intimacy between characters. All in all, this study details the ways silence informs narrative style, endows characters with psychological complexity, and enriches the subject matter of Tóibín’s Long Island.